2021
DOI: 10.3126/njhs.v1i2.42370
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Extended Spectrum β-Lactamases (ESBL) Producing Bacteria in Sepsis Suspected Neonates

Abstract: Introduction: Neonatal sepsis is a clinical syndrome that is caused when the bloodstream of an infant is invaded by bacteria in the first month after birth. Objective: The objective of the study was to identify bacteria involved in the infection and to determine “extended-spectrum beta-lactamase” (ESBL) producing bacteria from blood samples of sepsis suspected neonates in the Neonatal Intensive Care Unit and Special Care Baby Unit. Methods: This cross-sectional study was conducted from January to July 2019 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Hence, the prevalence of neonatal sepsis was 17%. A similar finding was reported by Yadav et al (2018) and Nepal et al (2021) where the prevalence rate of neonatal sepsis was 16.9% and 21.05% respectively. Few research depicted a higher incidence rate of neonatal sepsis in other developing countries such as Bangladesh (34.88%), Uganda 37%), Ethiopia (44.7%), and Nigeria (45.9%) (Shehab El-Din et al 2015) while lower incidence rate was depicted in Southern Africa (9.8%) (Mudzikati and Dramowski, 2015), Nepal (12.6%) (Ansari, 2015) and Pakistan (8.9%) (Raha et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Hence, the prevalence of neonatal sepsis was 17%. A similar finding was reported by Yadav et al (2018) and Nepal et al (2021) where the prevalence rate of neonatal sepsis was 16.9% and 21.05% respectively. Few research depicted a higher incidence rate of neonatal sepsis in other developing countries such as Bangladesh (34.88%), Uganda 37%), Ethiopia (44.7%), and Nigeria (45.9%) (Shehab El-Din et al 2015) while lower incidence rate was depicted in Southern Africa (9.8%) (Mudzikati and Dramowski, 2015), Nepal (12.6%) (Ansari, 2015) and Pakistan (8.9%) (Raha et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…K. oxytoca were 100% resistant to Ampicillin followed by Piperacillin/tazobactam, Cefepime, Cefotaxime, Ceftazidime and Gentamicin with equal sensitivity of 29 (93.5%). Similar findings were reported where K. oxytoca were demonstrated to be 100% sensitive to Meropenerm and resistant to Cefotaxime 7(100%) and Ceftazidime 7(100%) (Nepal et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…21,22 The problem has been frequently accounted in developing countries such as Nepal, where the prevalence of MDR and ESBL-producing bacteria has increased over the past years. 23,24 There are some scattered studies that reported ESBL-KP in Nepal. However, these are not available in an organized form.…”
Section: Introductionmentioning
confidence: 99%